(3cJGH aj GdeaQOGJ GdWHjIs
(3ChdgG (B:s
(3ChfWdjhdjhf , gh fHGJ jbGd Efg GfaY TF ai GdLQGMGJ GdQWHI hgj CQHYI CfhGY CUaQ s
(3BNQgG (B:s
(3Oadi , hjSei efg HQi hefg fgQi , hGdHQi hQbg echQ Hfi GdMeQI GOb bVHGfg WhGd GdGfgGQ hThcg Mafi hhQbI s
(3hgh eQJH Ydi MQha GdeYLes
(3Hg CSeGA fHGJGJ hYbGbjQ hCYTGH hahGFOgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B25 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs